Transfer characteristics of nitrogen fixed by leguminous green manure crops when intercropped with maize in northwestern China - Rui LIU; Guo-peng ZHOU; Dan-na CHANG; Song-juan GAO; Mei HAN; Jiu-dong ZHANG; Xiao-feng SUN; Wei-dong CAO (Journal of Integrative Agriculture)
To ascertain the possibility of cultivating maize using biological nitrogen fixation (BNF) by leguminous green manure crops in maize/leguminous green manure intercropping systems, BNF and nitrogen (N) transfer were studied in Xining and Wuwei, two typical northwestern Chinese cities. The experimental treatments included monocultured maize, monocultured green manures (hairy vetch and common vetch), and their intercropping systems. The proportions of N derived from the atmosphere (%Ndfa) in intercropping systems were not significantly different from that in monocultured green manure systems at either experimental site, except for that in hairy vetch (HV) in Xining. The amount of N derived from the atmosphere (Ndfa) of common vetch (CV) significantly decreased from 1.16 and 1.10 g/pot in monoculture to 0.77 and 0.55 g/pot when intercropped with maize, in Xining and Wuwei, respectively, and the Ndfa of HV when intercropped significantly decreased from 1.02 to 0.48 g/pot in Xining. In the intercropping systems in Xining and Wuwei, the amounts of N transferred (Ntransfer) from CV to maize were 21.54 and 26.81 mg/pot, accounting for 32.9 and 5.9% respectively of the N accumulation in maize, and the values of Ntransfer from HV to maize were 39.61 and 46.22 mg/pot, accounting for 37.0 and 23.3%, respectively, of the N accumulation in maize. Path analysis showed that soil nutrient and green manure biomass were mainly related to Ndfa, and that δ15N had a primary relationship with Ntransfer. We found that 5.9–37.0% of N accumulation in maize was transferred from green manures, and that the N transfer ability to maize of HV was higher than that of CV. In conclusion, intercropping with leguminous green manures provided a feasible way for maize to effectively utilize biologically fixed N.